Menanamkan nilai identitas nasional melalui pendidikan kepada generasi muda di era globalisasi - Jayayuni, Muhammad Syamsun (Maliki Interdisciplinary Journal, 2025)
National identity is an important foundation in building the character and identity of a nation. In this case, education has a crucial role as a means that can strengthen and instill the values ​​of friendship in young people. In the era of globalization marked by the rapid flow of information and foreign culture, there is a risk of erosion of national identity among the younger generation. Therefore, an education system is needed that is able to act as a fortress to protect national identity by implementing a curriculum that emphasizes local values, culture, history, and national morals. Education not only aims to convey knowledge, but also functions as a strategic means that forms character, attitudes, and awareness of nationalism. The role of teachers, lecturers, and other educators is very important as role models in instilling national values. In addition, support from family and society is needed to create an atmosphere that helps form a national identity. Through proper education, it is hoped that the younger generation can understand, appreciate, and preserve the nation’s culture and feel proud of their national identity. Cooperation between educational institutions, government, and society is needed to create an education system that is appropriate and responsive to the challenges of globalization. In this way, education will be the main foundation in creating a generation that is not only academically smart, but also has a strong identity and national spirit as part of the Indonesian nation.